Tinjauan Ekonomi, Politik dan Keamanan Terhadap Pengembangan Food Estate di Kalimantan Tengah Sebagai Alternatif Menjaga Ketahanan Pangan di Tengah Pandemi Covid-19 - Sianipar , Binsar; Tangkudung, Audrey G. (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
Since March 2020 Indonesia has been declared as an area that has been affected by the Covid-19 pandemic. The Coronavirus as the cause of the pandemic, which was discovered for the first time in Wuhan, China, has quickly been spreading throughout the world such as in Italy, India, Iran, and Indonesia. This condition has put a number of countries in the world, including Indonesia, at the gates of economic recession. The Government of Indonesia has implemented a number of policies, including appointing the Minister for Defense to maintain national food security in order to survive from a recession that potentially coming through the food estate program in Central Kalimantan. On this basis, this study examines the development of food estates in Central Kalimantan as an alternative to maintaining food security amid the COVID-19 pandemic through three perspectives, namely economy, politics, and security. The discussion was conducted qualitatively with an epistemological approach based on the four pillars of food security established by the World Food and Agriculture Organization (FAO), namely availability, access, utilization, and stability.